2012
DOI: 10.1080/19440049.2011.627573
|View full text |Cite
|
Sign up to set email alerts
|

Online detection and quantification of ergot bodies in cereals using near infrared hyperspectral imaging

Abstract: The occurrence of ergot bodies (sclerotia of Claviceps purpurea) in cereals presents a high toxicity risk for animals and humans due to the alkaloid content. To reduce this risk, the European Commission fixed an ergot concentration limit of 0.1% in all feedstuffs containing unground cereals, and a limit of 0.05% in 'intervention' cereals destined for humans. This study sought to develop a procedure based on near infrared hyperspectral imaging and multivariate image analysis to detect and quantify ergot contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…Vermeulen et al reported that spectra in a pixel are often a mixture of the pure constituent spectra. 34 Spectra acquired in the central part of crop residues were not affected by this phenomenon because crop residues are quite large elements and it was easy to acquire pure spectra on it. This confusion due to the low spatial resolution of the instrument and the mix of spectra was also well observed on predicted images of roots.…”
Section: Resultsmentioning
confidence: 99%
“…Vermeulen et al reported that spectra in a pixel are often a mixture of the pure constituent spectra. 34 Spectra acquired in the central part of crop residues were not affected by this phenomenon because crop residues are quite large elements and it was easy to acquire pure spectra on it. This confusion due to the low spatial resolution of the instrument and the mix of spectra was also well observed on predicted images of roots.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, Delwiche and Gaines (2005), working with single kernel reflectance from two spot-illuminated, fiber optic conveyance spectrometers arrived at the same conclusions as Polder's group. Elsewhere, Vermeulen et al (2012) described the use of HSI to detect ergot bodies (sclerotia of the fungus Claviceps purpurea) among raw grain. Very recent work by Senthilkumar et al (2017) documents the use of HSI to classify ochratoxin A (produced by Penicillium spp.)…”
Section: Introductionmentioning
confidence: 99%
“…NIRM imaging is a type of NIR imaging and has better spatial resolution. In the past decade, NIR imaging has become a powerful analytical tool for detecting contaminants and defects in agrofood products [19][20][21][22][23][24][25]. For feed products, several investigations have been conducted on the feasibility of using NIRM to detect, identify, and quantify processed animal byproducts [26][27][28][29][30] and on using NIR imaging for the complete screening of compound feeds [31].…”
Section: Introductionmentioning
confidence: 99%